A Competency Development Model Utilizing the Competency House Application: Evidence from a Provincial Health Office - Udin Hamim; Irawati Alinti (Indonesian Scientific Publication, 2026)
This study examines the effectiveness of employee competency development through the use of the Competency House Application at the Gorontalo Provincial Health Office. The topic is important because competency development among civil servants remains suboptimal despite the availability of a digital platform designed to support structured and continuous learning. The study addresses the central research question: how is competency development implemented through the application, and what factors hinder its effectiveness? The novelty of this paper lies in its empirical investigation of a digital competency system within a provincial-level public health institution, an area that has received limited scholarly attention in Indonesia. What is new in this study is the integration of digital competency mapping with real organizational constraints in a public-sector health context, offering insights not documented in prior research. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis to explore implementation practices and identify barriers. The findings show that the application has not been effectively used for competency planning, monitoring, and evaluation due to limited digital literacy, inadequate socialization, insufficient technical and human resource support, minimal leadership commitment, and a weak culture of self-directed learning. The study concludes that optimizing the application requires stronger digital infrastructure, continuous training, systematic socialization, and greater managerial involvement. These results imply that digital platforms can enhance competency-based human resource management when supported by sufficient organizational readiness. The most important implication is that strengthening digital capability and leadership commitment can transform competency development systems and improve public-sector performance.